Media Edukasi Berbasis Web Sebagai Upaya Pendukung Pendidikan Karakter Berdasar nilai Kearifan Lokal Pada Pusat Pengembangan Anak Light Generation - Gabriela Brissa Pitaloka; Simfony Sophie; Veronika Verasita Melani; Yogi Evan Dwi Kristantyo; Jong Jek Siang (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2021)
PPA Light Generation is one of the Compassion Foundations under the Pentecostal Church in Indonesia Hagios Family Yogyakarta which helps children with poor backgrounds. There are approximately 200 children from various Tribes, Religions, Races, and Intergroups from the age of 1 to 22 years who are sheltered by PPA Light Generation. The form of learning activities focuses on the formation of character and personality in children who are guided by noble values. In addition, the skills and talents of each fostered child are also considered. Coaching involves fostered children and mentors which is carried out regularly every week in the church. However, since the Covid-19 pandemic, physical meetings and material sharing cannot be carried out. The service output is